Dinamika Pengakuan Negara dalam Hukum Internasional : Analisis Implikasi Hukum dan Politik terhadap Kedaulatan Negara - Jessica; Ester Nathania Davita Sitanggang (Jurnal Hukum Lex Generalis, 2025)
The recognition of a state is the acknowledgment that a unit, born and recognized, has met the requirements set by international law to be considered a state, thus recognized as a legal entity in international law and society. The emergence of a new state as a result of a peaceful decolonization process generally does not pose issues regarding recognition. However, if the new state arises from rebellion, revolution, or a movement for independence, the act of granting recognition could have negative consequences, potentially straining relations with the parent state, which may perceive it as an affront or even as intervention. International law itself is explanatory or coordinative in nature and does not recognize hierarchical structures. Recognition can be categorized into several forms: de facto recognition, de jure recognition, collective recognition, conditional recognition, provisional recognition, ad hoc recognition, premature recognition, and curator recognition. In this context, the dynamics of state recognition in international law are often influenced by global and regional political contexts. Beyond the political aspects, in the framework of international law, states are the primary subjects, and recognition establishes a state's status and sovereignty as equal to other states on the international stage. When a state receives recognition from others, it can engage in international relations with those states.